The ideological function of characterization in Flann O'Brien's At Swim-Two-Birds - del Río Álvaro, Constanza (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
The purpose of this paper is first to establish the theoretical terms for an ideological analysis, not only of the messages contained in a narrative text, but also of a text's formal structures and narrative conventions. I then proceed to investigate the ideological function of characterization in Flann O'Brien's At Swim-Two-Birds (1939). That is, I consider the different subject positions encoded in the text's presentation and construction of its characters. Since this novel is a late-modernist experimental text, my intention is also to demonstrate that a departure from realistic convention does not necessarily lead to subversive and oppositional forms of reader-identification but may still be enforcing a traditional notion of authorship, a notion in which the figure of the author emerges as the omnipotent creator and guarantor of textual meaning.
Keywords: Flann O'Brien; characterization